Filmes e revestimentos comestíveis do polissacarídeo sulfatado da alga Marinha Vermelha Gracilaria birdiae na qualidade do camarão Litopenaeus vannamei congelado - Vieira, Claúdia Brandão (2019)
In recent years the interest in the development of edible and biodegradable films has been growing. Mostly because of the demand for high-quality food, environmental concerns about the disposal of non-renewable materials that are used as packaging for food and also as opportunities to create new markets of raw materials for elaboration of coatings, like carbohydrates, proteins, hydrocolloids, lipids, etc. The red macroalgae are rich in sulphated polysaccharides (SP), such as agar that is commercially prospected throughout the food industry and several researches have already been carried out, related to the elaboration of edible films and showed good mechanical and barrier properties. The present study aimed to characterize the SP extracted from the red algae Gracilaria birdiae through the DSC, TGA, FTIR analysis; to elaborate edible films based on this SP and to evaluate its physical and mechanical properties and scattering coefficient; to verify the antimicrobial activity of the film-forming solution and to determine the efficiency of the SP film in frozen, peeled and headless shrimp (Litopenaeus vannamei) through physico-chemical and microbiological analysis, as well as to evaluate shrimp, glazing and SP coating weight losses. DSC and TGA suggest that the SP of the present study is thermostable and can be used in the formation of biomaterials. The FTIR analysis detected the presence of functional groups characteristic of agarocoloids. WVP values increased with 0.1% glycerol concentration and the films were quite soluble in water. The films were luminous, slightly opaque and with a slight tendency to a yellowish-green coloration. The tension and deformation values during the rupture didn’t present significant differences (p<0,05). According to the scattering coefficient, the solution chosen was the one containing 1.0% SP and 0.0% glycerol. The concentration (1.0%) of SP tested showed no inhibition of bacterial growth. The pH, TBARS and TVB values of the shrimp samples presented significant differences (p<0,05) between treatments. SP-coated samples showed the lowest counts of psychrotrophic bacteria. The edible films elaborated in the present study have great potential as edible coatings and can be used to increase the shelf life of cooled fish, mainly because it is harmless to the consumer and biodegradable in the environment.